Coach knowledge in talent identification: A systematic review and meta-synthesis. Issue 10 (October 2019) - Roberts, Alexandra H.; Greenwood, Daniel A.; Stanley, Mandy; Humberstone, Clare; Iredale, Fiona; Raynor, Annette
Abstract: Objectives: Talent identification traditionally relies on the knowledge and perceptions of expert coaches to identify and predict potential future elite athletes. Experiential coach knowledge is a valuable source of information to guide research in this ill-defined and under-researched area. This review aims to synthesize current empirical understanding of coach knowledge as it relates to decision making in talent identification. Design: This systematic review and meta-synthesis used the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to identify relevant literature. Methods: Eligible studies were critically appraised for quality, and key findings from the 14 studies were integrated to allow for thematic analysis. Results: The meta-synthesis revealed the key theme of 'instinct' as the primary contributor to coach decisions during talent identification. Subordinate themes informing coach instinct were 'drive and ambition', 'game intelligence' and 'physical and technical skills'. Conclusions: Coaches appear to make decisions about talent based on their tacit knowledge or instinct. Understanding how coaches develop these instinctual 'feelings' may guide future research into talent identification and enhance our understanding of how experiential coach knowledge is developed and utilised in the daily training environment.